Developing Supplementary Material for Fast Learner in Ninth Grade Students of Junior High School at Buleleng Regency - Ni Nyoman Tri Andini Putri (Jurnal Penelitian Mahasiswa Indonesia, 2023)
Fast Learners have a high intelligence in following and understanding learning. Therefore, the activity used in the class affects the attainment of learning of fast learners. This study aims to develop supplementary material for fast learners in ninth grade SMP Negeri 6 Singaraja in Buleleng District. Materials developed based on student needs. In addition, creative and innovative learning to improve English skills and 4C skills of students. The method used in this research is Design and Development by Richey & Klein (2007). This method has four stages of Analysis, Design, Development, and Evaluation. This study involves teacher and students as subjects. At the Analysis stage, the researcher use syllabus, and textbook as early reference in the process of creating supplementary material. At the design and development stage, the researcher develop blueprint and product. The Evaluation stage is as a quality measuring tool on the product that has been developed. Expert judgment and user review shows that the book is Good as a medium in learning. The supplementary material developed according to students’ need are expected to be able to give challenges and train the abilities of fast learners.